2002
DOI: 10.2134/jeq2002.1795
|View full text |Cite
|
Sign up to set email alerts
|

Application Technique and Slurry Co‐Fermentation Effects on Ammonia, Nitrous Oxide, and Methane Emissions after Spreading

Abstract: The aim of this study was to investigate the effect of different application techniques on greenhouse gas emission from co-fermented slurry. Ammonia (NH3), nitrous oxide (N2O), and methane (CH4) emissions were measured in two field experiments with four different application techniques on arable and grassland sites. To gather information about fermentation effects, unfermented slurry was also tested, but with trail hose application only. Co-fermented slurry was applied in April at a rate of 30 m3 ha(-1). Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
102
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(121 citation statements)
references
References 29 publications
16
102
2
1
Order By: Relevance
“…The amount of total organic G added each year varied depending on the N content of the materials collected and dry matter percentage of the slurries (Table 1). Similar results of varying G additions have been reported by others (Fangueiro et al, 2008b;Rochette et al, 2006;Wulf et al, 2002). The total organic G added in 2008 was twice that of 2007, averaging 1380 kg G ha"' for LM in 2007 and4295 kg G ha"' in 2008.…”
Section: Carbon and Nitrogen Characteristics Of The Anaerobically Digsupporting
confidence: 85%
See 2 more Smart Citations
“…The amount of total organic G added each year varied depending on the N content of the materials collected and dry matter percentage of the slurries (Table 1). Similar results of varying G additions have been reported by others (Fangueiro et al, 2008b;Rochette et al, 2006;Wulf et al, 2002). The total organic G added in 2008 was twice that of 2007, averaging 1380 kg G ha"' for LM in 2007 and4295 kg G ha"' in 2008.…”
Section: Carbon and Nitrogen Characteristics Of The Anaerobically Digsupporting
confidence: 85%
“…Daily CH^ fluxes among treatments averaged -0.66 g CH^-C ha"' d~' in 2007 and -0.79 g CH^-C ha"' d~' in 2008, exclusive of the period associated with manure amendments. These seasonal uptake rates are lower than some values reported in the literature, with ranges of -6.4 to -13 g m-2 d-' (Phillips et al, 2009;Wulf et al, 2002). Haile-Mariam et al (2008) reported -1.4 g CH^-C ha"' d"' from irrigated soils cropped to potato {Solanum tuberosum L.) or sweet corn during the crop season ( 125 d).…”
Section: Methane Carbon Emissionsmentioning
confidence: 62%
See 1 more Smart Citation
“…The reported effects of manure treatments on nitrous oxide emissions are variable. Some authors reported similar N 2 O emissions from raw compared to anaerobically digested manure [18], others have reported decreased emissions after anaerobic digestion [13,19,20]. Conversely, Chantigny et al [7] reported increased emissions from digested compared to raw liquid swine manure, when the manures were injected into the soil.…”
Section: Introductionmentioning
confidence: 99%
“…In general, emissions are lowest when digestates are injected directly into soils. Higher emissions occur with close to the ground spreading techniques like trailing shoe or hose and highest when digestates are applied through splash plate (Wulf et al, 2002;Nkoa, 2013).…”
Section: Nitrogen Lossesmentioning
confidence: 99%